THE ISLAMIC ECONOMICS PHILOSOPHY AND APPLICATION REALITY IN THE EXISTING ISLAMIC ECONOMIC ACTIVITIES IN THE WORLD - Bhuiyan, Abul Bashar; Ismail, Abdul Ghafar; Nor, Mohd Zakhiri Bin; Ali, Md. Jafor; Solaiman, Mohammad (International Journal of Shari’ah and Corporate Governance Research, 2020)
Islam offers the complete code of human life. It is applicable in every sphere of life, whether business, service or any other occupations. Islamic Economic philosophy simply expounds or refers to philosophical activity within the Islamic paradigm. The main direction of Islamic philosophy provides a complete way of life based on al-Adl and al-Ihsan. The discussion on Islamic economic philosophy issues had started earlier and flourished when Muslim scholars dominated the world scientific development tradition. However, the economic issues are mainly solved by different branches and schools of economics thoughts. Therefore, this paper has an attempt look into the philosophical issues in the area Islamic economics and its comprehensive application in the existing economyall over the world. It is a purely descriptive presentation on the issues of Islamic economic philosophy. The study findings revealed that Islamic economic has a strong philosophical foundation where socioeconomic development can be done based on al-Adl and al-Ihsan. The study also concluded that al-Adl and al-Ihsan would be establish while economic life is directed by not only material motives but also consent of Allah and craving for happy eternal life in the hereafter.